THE EFFECT OF TRUST AND SATISFACTION AND COHESIVITY ON TEAM EFFECTIVENESS IN THE HUMAN RESOURCES DEVELOPMENT AGENCY OF EAST KALIMANTAN PROVINCE - Rina Kusharyanti; Djoko Setyadi; Irsan Tricahyadinata (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to determine what factors influence the increased effectiveness of the team at the Human Resources Development Agency of East Kalimantan Province. This study uses a cross-sectional design that is data collection that is conducted one time at a predetermined respondent with data analysis used is the partial least square (PLS) approach. A high level of trust will have a positive effect on the greater team effectiveness, so that at the same time team members will feel satisfaction in working with the group which will then affect the success of the team to achieve group goals. Thus, the more team members who are satisfied with the team, the better the performance of the interdependent team in completing the given task.